Spatial correlations of charm and anticharm quarks at hadronisation - Marek Gazdzicki; Daniel Kikoła; Ivan Pidhurskyi; Leonardo Tinti (Communications Physics)
Abstract Heavy-ion collisions offer a unique tool for studying the properties of strong interactions at high energy densities. An open question is how heavy quarks, such as charm and bottom, thermalise in the dense matter created by these collisions. Here, we show that the momentum correlations of charm and anticharm hadrons produced in central heavy-ion collisions can provide direct information on the spatial correlations of charm-anticharm quark pairs at hadronisation. This is possible under conditions where only a single charm-anticharm pair is created, as expected in central lead-lead collisions at CERN Super Proton Synchrotron (SPS) energies. We introduce a method to correct the measured joint momentum distribution for smearing effects caused by hadronisation, making the results directly sensitive to spatial correlations. Using simulated data, we demonstrate that even a sample of limited statistics can distinguish between different spatial correlation scenarios. These results offer a novel test of heavy-quark production and transport models and are achievable with current detector technologies and beam intensities.